2013
DOI: 10.5539/ijps.v5n3p84
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Strengths and Weaknesses in Solving Work Problems: A Knowledge and Appraisal Personality Architecture (KAPA) Analysis of the Trait Conscientiousness and Self-Efficacy

Abstract: Our goal was to demonstrate the effect of personal strengths and weaknesses when solving work related problems among students enrolled in business courses. We predicted that each participant would uniquely activate personal knowledge (such as strengths and weaknesses) in situations idiosyncratically judged as relevant to his or her strength or weakness. 65 participants completed all the measures of a two-study program (37 participants in study 1 and 28 participants in study 2). At the outset of both studies, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Engineering students displayed relatively high (low) self-efficacy in those subsets of situations that they subjectively linked to positively (negatively) valenced knowledge that they possessed. This result, which to our knowledge is novel in the study of self-efficacy beliefs among students in higher education, replicates the pattern of results obtained in other domains (e.g., Artistico & Rothenberg, 2013;Di Blas et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Engineering students displayed relatively high (low) self-efficacy in those subsets of situations that they subjectively linked to positively (negatively) valenced knowledge that they possessed. This result, which to our knowledge is novel in the study of self-efficacy beliefs among students in higher education, replicates the pattern of results obtained in other domains (e.g., Artistico & Rothenberg, 2013;Di Blas et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Although not addressed in the present report, this question has been addressed in numerous prior studies using KAPA-model assessments whose structure paralleled the methods used here. In research on both addictive behaviors (Cervone et al, 2007) and coping with workrelated problems (Artistico & Rothenberg, 2013), self-efficacy appraisals were not assessed until 1 week after assessments of self-schemas and situational beliefs. In research relating knowledge structures to contextualized patterns of self-efficacy appraisal across a wide range of everyday circumstances, self-efficacy was assessed 2 weeks after prior assessments (Cervone, 1997(Cervone, , 2004.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ehrenberg et al defined conscientiousness to be an individual's ability to be careful and efficient which lead to improving task performance [48]. Other studies found that those who demonstrate high levels of trait conscientiousness are better performers than those who do not [49][50]. Conscientiousness has been known to be the strongest predictor of performance across multiple measures as stated by Neal et al [51].…”
Section: Introductionmentioning
confidence: 99%
“…Its assessment principles (Cervone, Shadel, & Jencius, 2001) facilitate identification of these patterns and their underlying causes (reviewed in Cervone, 2008;Cervone & Quirin, 2017). Researchers have employed KAPA-model theoretical principles and assessment methods to advance three other goals discussed by Baumert and colleagues: testing causal processes experimentally (Artistico & Rothenberg, 2013;Cervone et al, 2008), intervening for behavioral change (Scott & Cervone, 2016), and accounting for within-person variability while empirically integrating between-person and within-person methods (Di Blas, Grassi, Carnaghi, Ferrante, & Calarco, 2017).…”
Section: Cognitive Structures Countmentioning
confidence: 99%